2017
DOI: 10.1111/phpp.12361
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the visual appearance of sunscreens applied to the skin using indirect computer image colorimetry

Abstract: Standardized sunscreen application followed by digital photography and indirect computer-based colorimetry represents a potential method to objectively quantify visibility of sunscreen on the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…A professional Macbeth color chart (Spyderchekr 24; Datacolor, Trenton, NJ, USA) [ 5 , 39 , 41 , 42 ] was positioned in the place of the 18% gray card and the images were repeated within each environmental condition following the same procedure. However, photographs with Macbeth color chart were not done as the photo box cast uneven shadows onto the color charts and could potentially skew the data.…”
Section: Methodsmentioning
confidence: 99%
“…A professional Macbeth color chart (Spyderchekr 24; Datacolor, Trenton, NJ, USA) [ 5 , 39 , 41 , 42 ] was positioned in the place of the 18% gray card and the images were repeated within each environmental condition following the same procedure. However, photographs with Macbeth color chart were not done as the photo box cast uneven shadows onto the color charts and could potentially skew the data.…”
Section: Methodsmentioning
confidence: 99%
“…The subject is illuminated by either UV emitting lamps or sunlight, and a photo is taken, which then highlights the areas where sunscreens have been applied. Sunscreen application followed by UV photography is a potential method to objectively measure the visibility of sunscreen on the skin [ 1 ]. Pratt et al [ 2 ] have shown that UV photography can detect commonly missed areas during sunscreen application on the face, with participants missing the eyelids and the medial canthal area around the eyes.…”
Section: Introductionmentioning
confidence: 99%